The Role of Islam in the Development of the 'Belt and Road' Initiative. Issue 1 (2nd January 2018) - Li, Fuquan
Abstract: Historically, the interaction between the religion and trade has not only promoted the expansion of Islam along the Land and Maritime Silk Road, but also developed a close relationship between China and the Islamic world. Now Islam is one of the most influential and widely distributed religions in the world. Being in the core sections of Land and Maritime Silk Road, the Middle East, Central Asia, South Asia, and Southeast Asia are the areas where Islam is a dominant religion. Therefore, for China, good relations with Islamic countries are very critical for the successful implementation of the 'Belt and Road' Initiative. China's over 23 million Muslims (especially the Hui People) know two cultures (Chinese and Islamic), have two identities (Chinese and Muslims), and are the natural bridge between China and Islamic countries. Chinese Muslims are playing an important role in the development of Islamic finance and production of Muslim licit (halal) food products which are two potential cooperation areas between China and Islamic countries. For China and Islamic countries, it is necessary to expand cultural exchanges to eliminate some misunderstandings of each other.